Pengembangan Mesin Pelet Tenaga Surya untuk Mengurangi Biaya Pakan Ikan Bagi Petani Tambak di Desa Juwiring Kabupaten Kendal - Firman Ardiansyah Ekoanindiyo; Yohanes, Antoni; Amin, Imam Husni Al; Khristianto, Teguh; Retnowati, Retnowati (ABIDUMASY, 2026)
The fish farming group in Cepiring District, Kendal Regency, faces a major issue of high fish feed costs, which amount to approximately IDR 4,500,000 per harvest cycle. Dependence on external suppliers causes unpredictable price fluctuations, hindering the increase in farmers' income. Therefore, it is essential to find a solution that can significantly reduce production costs. The objective of this community service program is to reduce fish feed production costs by developing a solar-powered pellet machine, which can independently produce fish feed using renewable energy. The service partner in this program is the Fish Farming Group in Cepiring District, Kendal. The method of this service includes problem analysis, development of solar-powered pellet machine technology, technical training on how to use and maintain the machine, and the implementation of digital marketing to improve market access. The expected outcomes are a 40-50% reduction in fish feed costs per harvest cycle, increased independence for farmers in producing their own fish feed, and improved overall production efficiency. This program is expected to support the sustainability of environmentally friendly fish farming and enhance the economic independence of fish far.